STUDI PERTUMBUHAN, PRODUKSI DAN NILAI EKONOMIS IKAN MAS (Cyprinus carpio Lin.) DENGAN MENGGUNAKAN PAKAN BUATAN NON KOMERSIL - Abdul Muis Balubi; Irdam Riani; Ngadiyo Ngadiyo (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
Feed is one of the key factors for the success of carp cultivation. But the price of feed on the market is quite expensive, causing farmers to reduce the amount of feed. The impact is that the amount of goldfish production is low. This study aims to determine the growth, production and economic value of carp (C. carpio Lin.) Using non-commercial artificial feed. This research was conducted in May-August 2016 at Rakawuta Village, Mowila District, South Konawe Regency, Southeast Sulawesi Province. The study design used was a randomized block design with 5 treatments and 3 replications. The results showed that the treatment of non-commercial artificial feed had a significant effect on absolute growth, specific growth rates, survival rates, production and some economic values. The absolute growth of individuals and the highest specific growth rate resulted in treatment B of 204.04 gr / head (4.38%) and the lowest treatment of 100% commercial feed with absolute growth of 92.80 gr / head (3.09%). The highest survival and production was produced by B at 96.67% (94.75 kg) and the lowest treatment D with survival of 92.89%, while the lowest production resulted in treatment E of 45.74 kg. The highest economic value in the form of a Cost Ratio and Payback period resulted in treatment B amounting to 6.16 with a Payback period of Rp1,894,980 and the lowest treatment E with a cost ratio of 2.97 payback period of Rp914,780. Non-commercial feed use of artificial has not fully provided important growth, production, and economic value for farmers.